STRATEGI PELAKU BISNIS RITEL DALAM MENGEMBANGKAN PRODUK PRIVATE LABEL - LIEM, RENDY NOVANDA SUMANTO (Kajian Ilmiah Mahasiswa Manajemen, 2013)
This discussion paper aims to provide an understanding of the retail business strategy in the development of private label. It is a subject that objectives are being achieved is the development of private label to build brand image and strategy of the retail businesses in developing private label.Can be developed by the private label retail businesses by leveraging the power of the brand image held. Ability to develop private label will bring in the ability to extend the product to be offered to consumers so that the opportunity to build a brand image. Retail business person should choose the right strategy, in order to successfully achieve the goals of private label development. The selection of the right product to be developed in private label sales is important, because not all products can be sold with private label. Another thing to consider is the ability to create customer satisfaction and create competitive advantage, because it can increase positive brand image to attract consumers to products with private label sales.